PENINGKATAN PENDAPATAN PETANI KARET MENGGUNAKAN CABAI RAWIT (Capsicum frutescens Linn.) SEBAGAI TANAMAN SELA (Studi Kasus Di Desa Sembawa, Kecamatan Sembawa, Provinsi Sumatera Selatan) - Sahuri (Talenta Publisher, 2017)
One alternative effort in order to increase the income of smallholders on immature rubber period was by practicing rubber based mix-cropping with other supporting plants. This research was conducted to observe the growth of girth and the enhanced income of smallholder using cayenne pepper as intercrops with the application of recommendation technology. This study was carried in dry land between rubber trees in Sembawa Village, Sembawa District, South Sumatra from June until October 2014. The treatment was of recommended technologies and farmer’s technologies. The results showed that the application of recommended technologies was significant effect on rubber growth, number of branches, fresh fruit production/plant, and fresh fruit production/1000 m2 ha except for plant height and harvesting time. However, overall the recommendation technology was better than farmer technology. Production of fresh fruit at 650,5 kg /1000 m² higher than farmer technology by 348,9 kg/1000 m². Gains derived by application of cayenne pepper farming technology recommended by IDR 5.456.000/1000 m² larger than IDR 2.704.200/1000 m² farmer technology with the B/C ratio of 1.27 and farming is feasible to be developed with MBCR value of 1.55.